1997
DOI: 10.1128/aem.63.11.4158-4163.1997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactobacilli on yeast-catalyzed ethanol fermentations

Abstract: Normal-gravity (22 to 24°Plato) wheat mashes were inoculated with five industrially important strains of lactobacilli at ϳ10 5 , ϳ10 6 , ϳ10 7 , ϳ10 8 , and ϳ10 9 CFU/ml in order to study the effects of the lactobacilli on yeast growth and ethanol productivity. Lactobacillus plantarum, Lactobacillus paracasei, Lactobacillus #3, Lactobacillus rhamnosus, and Lactobacillus fermentum were used. Controls with yeast cells but no bacterial inoculation and additional treatments with bacteria alone inoculated at ϳ10 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0
16

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(75 citation statements)
references
References 20 publications
6
53
0
16
Order By: Relevance
“…The effects of lactobacilli contamination have been extensively studied in the laboratory. It has been generally believed that lactobacilli cause inhibition of Saccharomyces or limit ethanol production through two basic methods; either production of lactic and acetic acids or through competition for nutrients (Narendranath et al 1997;Narendranath 2003). However, a number of researchers have demonstrated that these mechanisms may not completely account for this inhibition.…”
Section: Effects Of Lactobacilli Contamination On Biofuel Fermentationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of lactobacilli contamination have been extensively studied in the laboratory. It has been generally believed that lactobacilli cause inhibition of Saccharomyces or limit ethanol production through two basic methods; either production of lactic and acetic acids or through competition for nutrients (Narendranath et al 1997;Narendranath 2003). However, a number of researchers have demonstrated that these mechanisms may not completely account for this inhibition.…”
Section: Effects Of Lactobacilli Contamination On Biofuel Fermentationsmentioning
confidence: 99%
“…While it is true that acetic acid formation is associated with aerobic growth of D. bruxellensis (Narendranath et al 1997;Abbott and Ingledew 2005;Blomqvist et al 2010), there is not enough produced to completely explain the drop in ethanol production (Abbott and Ingledew 2005). Additionally, D. bruxellensis grows more slowly and therefore does not present itself as a contaminant until later in the fermentation (Abbott and Ingledew 2005).…”
Section: Dekkera Bruxellensis Contaminationmentioning
confidence: 99%
“…4 The abundance of LAB strains in silages depends on several factors, including preparation conditions, time of harvesting and duration of silage preparations. 14 The strains showed different biochemical characteristics relative to each specific species. On the basis of biochemical properties, L. plantarum strains could be divided into two groups: nine L. plantarum strains grew in D-arabinose but did not grow in the presence of D-arabinose; in contrast, none of the L. plantarum strains grew on L-arabinose.…”
Section: Discussionmentioning
confidence: 99%
“…LF, a heterofermentative organism, is the most predominant contaminant in industrial fermentation in Brazil (Costa et al 2015) and can cause yeast flocculation capable of decreasing the bioethanol production (Dellias et al 2018). LPC has been shown to possess the ability to produce levels of lactic acid that can result in more than 2% reduction in ethanol production even at a low level of inoculation (10 8 CFU per litre) (Narendranath et al 1997). Although there are few reports about LPP and LG contamination effects, the LPP and LG strains used in this study were isolated from sugarcane and cider respectively, and show a very strong acid resistance (Daum 2016).…”
Section: Effects Of Acid Wash and Acid/nisin Wash On The Viabilities mentioning
confidence: 99%